Penetrasi Trakea: Serangkaian Kasus Strategi Penanganan Trauma Leher Akibat Trauma Tembus - Steven Lonardo Geritz Korobitua; Nico A. Lumintang; Sherly Tandililing (Jurnal Ventilator, 2026)
Penetrating neck trauma (PNT) is a critical surgical emergency, accounting for 5-10% of traumatic injuries. The neck’s compact anatomy, housing vital vascular, aerodigestive, and neurological structures, makes penetrating injuries immediately life-threatening. Tracheal injuries, though rarer than vascular ones, are particularly lethal due to their potential to obstruct the airway. Management has shifted from mandatory exploration to selective non-operative management (SNOM) based on clinical assessment and advanced imaging, particularly computed tomography angiography (CTA). However, "hard signs" like active hemorrhage, expanding hematoma, or subcutaneous emphysema still warrant immediate surgical intervention. This case series discusses the management of three distinct penetrating tracheal trauma presentations. Case I: A 32-year-old male with a Zone II neck stab wound from a kitchen knife. Case II: A 22-year-old male with a 3x2 cm Zone I stab wound. Case III: A 16-year-old male with a penetrating cervical wound from an arrow. All patients survived and were discharged successfully. The Case I patient, stable with Zone II injury, had an uncomplicated recovery and decannulation by day 14. The Case II patient, unstable with Zone I injury, was stabilized and underwent surgical airway management. The Case III patient, stable throughout, underwent successful exploration and debridement and was discharged on day 6. These cases demonstrate the effectiveness of a structured approach prioritizing ATLS principles, timely surgical intervention, and adaptability to injury characteristics, ensuring positive outcomes for penetrating tracheal trauma.